A Combined Effective Time Dependent Matrix Approach to Analyze the Men Affected by Cardiovascular Disease (CVD) in Chennai (International Journal of Engineering and Computer Science, 2015)
The objective of this paper is to find out the peak age of Men affected by cardiovascular disease in Chennai. For thatwe have collected the data and analyzed the same disease. For the first time in 1998, fuzzy matrix theory was developed byW.B. Vasantha and V. Indira to study the passenger transportation. To study this problem, they divided and defined four typesof matrices called Initial Raw Data Matrix, Average Time Dependent Data matrix (ATD Matrix), Refined Time DependentData matrix (RTD Matrix) and Combined Effect Time Dependent Data Matrix (CETD Matrix). In the year 2003 the sametechnique was used by W.B. Vasantha to study the migrant laborers who were affected by HIV/AIDS. In 2012 and 2013, A.Victor Devadoss, M. Clement Joe Anand and A. Felix have studied dimensions of personality of men and women separatelyusing this model. A CETD Matrix Approach to analyze the dimensions of personality of person in 2014 by the same authors.Now we use this model to study the Men affected by cardiovascular disease in Chennai.